Improved potatoes to boost climate resilience in Kenya and Peru. Project profile. - International Potato Center (International Potato Center, 2019)
Wild relatives of staple crops often have useful traits that can be bred into the more productive varieties to sustain yields when the plants are subject to challenging growing conditions. This project aims to improve farmers’ climate resilience by identifying useful genes in wild relatives of potato and breeding new strains with good resistance to drought and late blight disease.